2006
DOI: 10.1063/1.2232199
|View full text |Cite
|
Sign up to set email alerts
|

The role of the ring nitrogen and the amino group in the solvent dependence of the excited-state dynamics of 3-aminoquinoline

Abstract: The nonradiative rate in 3-aminoquinoline is found to exhibit anomalous solvent dependence, being rather fast in nonpolar solvents and remarkably slower in more polar and especially, more protic ones. The cause of such behavior is investigated by studying the dependence of fluorescence spectral and temporal parameters on the solvent properties such as polarity and hydrogen bonding ability. Complementary quantum mechanical calculations have been performed and the picture that emerges from these studies is that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 42 publications
(52 reference statements)
5
28
0
Order By: Relevance
“…In most solvatochromic studies, Δf, which is a measure of the orientational polarizability of the solvent, is considered to be a good parameter for correlating the effects of solvent polarity with the observed photophysics ,,. This is based on the understanding that since electronic polarization is an instantaneous process, it is not reflected in the photophysical properties which are mainly governed by reactions and interactions taking place during the excited state lifetime of the chromophores .…”
Section: Resultsmentioning
confidence: 99%
“…In most solvatochromic studies, Δf, which is a measure of the orientational polarizability of the solvent, is considered to be a good parameter for correlating the effects of solvent polarity with the observed photophysics ,,. This is based on the understanding that since electronic polarization is an instantaneous process, it is not reflected in the photophysical properties which are mainly governed by reactions and interactions taking place during the excited state lifetime of the chromophores .…”
Section: Resultsmentioning
confidence: 99%
“…Datta et al showed that the ICT emission of 3-aminoquinoline (20) was favored in aprotic solvents such as dimethyl sulfoxide by a similar type of hydrogen bonding (21). 56 On the other hand hydrogen bonding inhibits the ICT emission of 20 in protic solvents, where the charge donor acts as a hydrogen bond acceptor 22, but the protonation of the acceptor enhances the ICT process (23).…”
Section: Role Of Hydrogen Bonding With An Electron Donormentioning
confidence: 99%
“…The data are fitted to multiexponential functions after deconvolution of the instrument response function by an iterative reconvolution technique, using the IBH DAS 6⋅0 data analysis software, where reduced χ 2 and weighted residuals serve as parameters for goodness of fit. 9 Time-dependent anisotropy, r(t), is constructed from the decays in the parallel and perpendicular directions to that of the excitation polarization (I || (t) and I ⊥ (t) respectively) as:…”
Section: Time-resolved Measurementsmentioning
confidence: 99%